Stealth humanitarianism: negotiating politics, precarity and performance management in protecting the urban displaced - Kihato, CW; Landau, LB (Oxford University Press, 2016)
Post-cold-war-era conflicts and the humanitarian political economy have driven two disparate yet concurrent shifts within the humanitarian field. On one hand, new public management-style reforms have increasingly focused organizations on efficiency, deliverables and technical proficiency. On the other, an international rights regime has demanded that humanitarian interventions and actions become more explicitly political. Nowhere are the tensions between neutral humanitarian expertise and the need for overt political engagement more visible than for organizations promoting refugee protection in fluid, politically pluralistic urban sites. Building on fieldwork in Johannesburg, Kampala and Nairobi, we argue that neutrality, technical fixes and demands for direct and targeted service delivery can undermine long-term urban protection. Rather, protection requires enhanced local literacy and pursuing back routes to rights through engagement with municipal authorities, local actors and policy sectors. In other words, humanitarian organizations must work smarter, smaller and stealthier. But, to do this, the sector requires substantial shifts in its funding regime—including reconsidering demands for measurable outputs, strictly targeted services and rapid direct service delivery.